LOW CRYSTALLINITY NANOHYDROXYAPATITE PREPARED AT ROOM TEMPERATURE - MOCANU, Aurora; BALINT, Reka; ISTRATE (GARBO), Corina; TIMIȘ, Lucia Iacobina; PETEAN, Ioan; HOROVITZ, Ossi; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2017)
In order to obtain a low crystalline nanohydrxyapatite (HAP), suitable for biomedical application, a new synthesis procedure was developed, based on the aqueous precipitation method, at room temperature, without any additives. Accordingly, lyophilized HAP powders, both calcined and non calcined, were prepared, and characterized by XRD, TEM and AFM imaging, FTIR spectroscopy, zeta potential and BET measurements. The results confirmed HAP as the only phase present. The high porosity of this nanomaterial is attained. The nanoparticle size and shape as well as the crystallinity degree of the obtained HAP samples were also determined.